Diagnostic approach to Haematologic Malignancies in Resource-Limited Settings- A Review - Elujoba O. Samson1,2*, Ibrahim Adamu1,3. Igbe Mba1,4, Adepoju Emmanuel1,5, Babajimi-Joseph Amarachi1,6, Muhibi Musa1 Department of Medical Laboratory Sciences (Sokoto Journal of Medical Laboratory Science)
Haematologic malignancies encompass a diverse group of cancers originating in the blood, bone marrow, and lymphatic system. Such diseases pose a significant health burden in Africa. This review provides a comprehensive overview of these malignancies, focusing on classification, diagnosis, treatment strategies, and prognosis determination in resource-constrained settings. We delve into the types leveraging on World Health Organization (WHO) classification system and other literatures. Diagnostic approaches encompassing morphology, immunophenotyping and cytogenetics are elaborated upon. Limited access to modern diagnostic techniques often hinders early and accurate diagnosis, leading to poorer patient outcomes. Therefore, strategies to improve skills of laboratorians and clinicians in making optimum use of affordable technologies for the diagnosis and management of haematologic malignancies should be embraced by all, while jettisoning inter and intra-professional rivalry which has potential to impede quality health services in Africa.